Determinan Nilai Perusahaan Berdasarkan Kepemilikan dan Aspek Makro Ekonomi - Yusuf Yusuf (Universitas Pamulang, 2020)
The study aims to examine the effect of foreign ownership, institutional ownership and SOE ownership as well as the effect of inflation, exchange rates and interest rates on the value of financial sector companies. The population in this study are financial sector companies listed on the Indonesia Stock Exchange (IDX) and have provided audited financial statements at the end of the year from 2010 to 2014. Data analysis is done descriptively by calculating the average value, mode, median and others. The data is then processed using panel data regression with Eviews version 7 software. The results showed the Structure of Foreign Ownership and Institutional Ownership Structure affect the value of the company. BUMN ownership has no effect on company value. Inflation, exchange rate and interest rates do not affect the value of the company in the financial sector, this can occur because of Indonesia's macroeconomic conditions during the study period in a stable condition, there is no shock or crisis